2010
DOI: 10.1089/aid.2009.0289
|View full text |Cite
|
Sign up to set email alerts
|

HIV Infection Among U.S. Army and Air Force Military Personnel: Sociodemographic and Genotyping Analysis

Abstract: Since 1985, the U.S. Department of Defense has periodically screened all military personnel for HIV allowing for the monitoring of the infection in this dynamic cohort population. A nested case-control study was performed to study sociodemographics, overseas assignment, and molecular analysis of HIV. Cases were newly identified HIV infections among U.S. Army and Air Force military personnel from 2000 to 2004. Controls were frequency matched to cases by gender and date of case first positive HIV screening test.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…Some previous studies indicate STI prevalence rates among military personnel are higher than rates associated with the non-military population. Other studies found STI rates in military personnel are similar to those of the general population [2,3,15,16]. Within the armed forces, factors found to modify risk include: age, gender, race, marital status, length of military service, full time or reserve status, and rank.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Some previous studies indicate STI prevalence rates among military personnel are higher than rates associated with the non-military population. Other studies found STI rates in military personnel are similar to those of the general population [2,3,15,16]. Within the armed forces, factors found to modify risk include: age, gender, race, marital status, length of military service, full time or reserve status, and rank.…”
Section: Introductionmentioning
confidence: 88%
“…STI rates are influenced by the presence of active testing policies. A military with HIV/STI screening tests at entrance would admit fewer persons with prior HIV infection, thereby lowering the potential prevalence [15].…”
Section: Introductionmentioning
confidence: 99%
“…This was not unexpected as these findings are consistent with those in a previous report of the epidemic of HIV in the U.S. Army and Air Force. 2 However, these data demonstrate that HIV infection results in short-term morbidity and lost duty time in the combat environment. The realities of the current combat environment support the rationale that served as a basis for implementing force-wide screening policies 25 years ago.…”
Section: 13mentioning
confidence: 88%
“…The epidemic in the Army is similar to that in the U.S. general population; HIV infection disproportionately affects blacks and males and also disproportionately affects certain regions of the country including the South and Northeast. [2][3][4] By regulation, all U.S. soldiers are subject to periodic serologic screening for HIV every 2 years. In addition, soldiers who deploy to combat are also screened both prior to and after returning from deployments.…”
mentioning
confidence: 99%
See 1 more Smart Citation